Frontispiece: Ultrathin Covalently Bound Organic Layers on Mica: Formation of Atomically Flat Biofunctionalizable Surfaces. Issue 15 (3rd April 2017) - Sen, Rickdeb; Gahtory, Digvijay; Carvalho, Rui Rijo; Albada, Bauke; van Delft, Floris L.; Zuilhof, Han
Abstract : Surface Chemistry In their Communication onpage 4130 ff., H. Zuilhof et al. report the facile and covalent modification of mica by using a catechol‐based surface anchor with a flexibly linked amino group.